The Dynamics of Digital Counseling During the Covid-19 Pandemic - Balqis, Putri Keniza; Salsabiila, Robi’atur Rokhmah (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The advancement of information technology has introduced innovations in counseling services through digital platforms. This phenomenon became particularly relevant during the COVID-19 pandemic, when face-to-face interactions were limited. This study aims to analyze the dynamics of digital counseling use, focusing on digital counseling techniques from an Islamic perspective. A qualitative case study approach was employed, involving a single informant who participated in digital counseling during the pandemic. Data were collected through in-depth interviews and analyzed using data reduction and narrative presentation techniques. Findings indicate that digital counseling allows clients to receive guidance flexibly and effectively, enhances emotional regulation, resolves personal and academic issues, and encourages openness during counseling sessions. Techniques applied, including active listening, reflection, empathy, exploration, open-ended questions, and paraphrasing, effectively support interactive and adaptive digital sessions. Moreover, integrating Islamic values, such as dhikr and self-reflection, provides spiritual tranquility. This study concludes that digital counseling is not merely a substitute for face-to-face sessions but also a means of developing character, emotional skills, and mental well-being.